2019
DOI: 10.1039/c8sc05605f
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid room temperature synthesis of red iridium(iii) complexes containing a four-membered Ir–S–C–S chelating ring for highly efficient OLEDs with EQE over 30%

Abstract: Three red iridium(iii) complexes with dithiocarbamate ligands were rapidly synthesized at room temperature with good yields, and their OLEDs exhibit an EQEmax of 30.54% with mild efficiency roll-off.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…[ 25 ] In the aspect of ionic complex, the tetrahalide manganese(II) complex can be prepared quantitatively by mixing organic halogen salt and MnX 2 (X = Cl, Br, I) in a stoichiometric ratio in CH 2 Cl 2 , alcohol, water, or acids at room temperature; [ 22,44 ] the AMnX 3 ‐type coordination polymers could also be obtained conveniently by evaporation of the aqueous solution with stoichiometric amounts of organic salt or free base, MnX 2 , and excess of HX at room temperature. [ 35a,36 ] Compared with the noble metal‐based phosphorescent complex, [ 10–12 ] the synthesis of phosphorescent manganese(II) complex is much easier, and the target complex can be obtained in a high yield.…”
Section: Molecular Design Strategies Of Phosphorescent Manganese(ii) mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 25 ] In the aspect of ionic complex, the tetrahalide manganese(II) complex can be prepared quantitatively by mixing organic halogen salt and MnX 2 (X = Cl, Br, I) in a stoichiometric ratio in CH 2 Cl 2 , alcohol, water, or acids at room temperature; [ 22,44 ] the AMnX 3 ‐type coordination polymers could also be obtained conveniently by evaporation of the aqueous solution with stoichiometric amounts of organic salt or free base, MnX 2 , and excess of HX at room temperature. [ 35a,36 ] Compared with the noble metal‐based phosphorescent complex, [ 10–12 ] the synthesis of phosphorescent manganese(II) complex is much easier, and the target complex can be obtained in a high yield.…”
Section: Molecular Design Strategies Of Phosphorescent Manganese(ii) mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Quite different from the traditional fluorescent materials with the light emission from the singlet states, PTMCs are triplet emitters. [9][10][11][12][13][14] Since Forrest and coworkers successfully realized the first phosphorescent organic should be well noted that many phosphorescent manganese(II) complexes also exhibit ferroelectric properties. [35a,36] In this progress report, we mainly focus on the luminescent properties and related photofunctional applications of various phosphorescent manganese(II) complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the sulfur atom is able to stabilize metal ions in unusual oxidation states [ 13 , 14 , 15 ]. Therefore, it has a great advantage over the costly traditional way of refluxing the [(C^N) 2 Ir(μ-Cl)] 2 chloride-bridged dimers with cyclometalated or ancillary ligands at high temperature for a long time [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our former study, we prepared some red Ir(III) complexes using 4-(4-(trifluoromethyl)phenyl)quinazoline (4tfmpq) as the cyclometalated ligand. Diisopropylamine, diphenylamine, carbazole and their derivatives substituted dithiocarbamates as ancillary ligands at room temperature within 10 min, and the device performances were improved greatly [ 16 , 21 , 22 ]. Furthermore, from our investigation we found that the Ir-S-C-S structures were only valuable for the red Ir(III) complexes with excellent device performance.…”
Section: Introductionmentioning
confidence: 99%